Minimizing antibody cross-reactivity in multiplex detection of biomarkers in paper-based point-of-care assays. Issue 15 (31st March 2016) - Dias, J. T.; Lama, L.; Gantelius, J.; Andersson-Svahn, H.
Abstract : Sonication for mitigation of nonspecific interactions between antibody-modified gold nanoparticles improving detection in multiplexed point of care immunoassays. Abstract : Highly multiplexed immunoassays could allow convenient screening of hundreds or thousands of protein biomarkers simultaneously in a clinical sample such as serum or plasma, potentially allowing improved diagnostic accuracy and clinical management of many conditions such as autoimmune disorders, infections, and several cancers. Currently, antibody microarray-based tests are limited in part due to cross reactivity from detection antibody reagents. Here we present a strategy that reduces the cross-reactivity between nanoparticle-bound reporter antibodies through the application of ultrasound energy. By this concept, it was possible to achieve a sensitivity 10 3 -fold (5 pg mL −1 ) lower than when no ultrasound was applied (50 ng mL −1 ) for the simultaneous detection of three different antigens. The detection limits and variability achieved with this technique rival those obtained with other types of multiplex sandwich assays.